Psychological Aspects of Rheumatoid Arthritis: The Role of Depression in Pain Management - Vučković, Maja; Kožul, Dragana; Bojinović Rodić, Dragana; Tomašević-Todorović, Snežana; Trivunović, Sandra (Scripta Medica, 2025)
Background/Aim: Rheumatoid arthritis (RA) is a chronic autoimmune disorder that primarily affects the joints, leading to stiffness, swelling and persistent pain. Pain in these patients is not only a physical symptom but also a complex experience shaped by biological, psychological and social influences. Depression and anxiety frequently occur alongside the disease, further contributing to greater pain perception, reduced functional ability and diminished quality of life. Aim of this study was to highlight the impact of depression on functional status and pain intensity in female patients with rheumatoid arthritis. Methods: A descriptive analytical study involving 50 female patients diagnosed with RA according to ACR/EULAR criteria followed patients during inpatient rehabilitation at the Institute for Physical Medicine, Rehabilitation and Orthopaedic Surgery "Dr Miroslav Zotović" was performed. The study examined the relationship between pain (VAS), functionality (HAQ), depression (BDI) and personality disorders (MMPI). Results: The average age of participants was 63.8 years. The most common comorbidities were hypertension (64 %) and hypothyroidism (30 %). Of the total 50 patients, 23 (46 %) were smokers. The mean VAS pain scale value was 6.59, while the HAQ questionnaire average value was 0.811. Depression was identified in 17 patients (12 mild, 4 moderate and 1 severe depression). Patients with depression had higher pain intensity and poorer function. Conclusion: Psychosocial factors, including anxiety and depression, are important predictors of functional status and pain in RA. For effective pain management, it is important to identify, through a biopsychosocial approach, all factors that influence subjective pain perception.